The Nation and Its Logic in Early Twentieth-Century China - Shin, Leo (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractOf the radical transformations that have been associated with modern China, one of the most significant, historians would agree, is the permeation of the convictions — often with the aid of concepts borrowed from Europe via Japan — that Chinese people are inherently a nation (min zu) and that China is, by extension, a nation-state (guo jia). But as many have noted, the process of adopting and internalizing such convictions was far from linear. Taking as its point of departure the contested nature of the nationalist discourse and drawing particular attention to the border province of Guangxi, this paper seeks not only to identify the logic and fundamental tensions inherent in the construction of the nation (especially from the perspective of a border region) but also to explain why such tensions have continued to plague present-day China.